Implementasi Cerita Rakyat Kilat Tembilar pada Pertunjukan Tari Jung dalam Festival Sriwijaya di Sumatera Selatan - Muhammad Rizki Triandra; Kristoporus Dimas Revilco Okina Geozenda (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
Technological developments already influence children, so they are more focused on their gadgets. This is very influential with children's interest in folk tales conveyed by parents. The folklore of Kilat Tempilar is a story originating from Lubuklinggau, South Sumatra. The archipelago has past stories of various unique stories with heritage sites. Children, as early as possible should know their identity. Every child is born from diverse ancestry and different ethnicities. Each ethnic group in the archipelago has different customs or cultures. With the folklore-themed dance performances, it is hoped to revive Indonesian folklore that is not widely known by the public. Performing arts can be a medium for implementing folklore which is more easily imprinted in the audience's minds, and children will be more interested in performing arts which tell folk stories rather than listening to them orally from their parents without any examples in visual form. Implementing the Kilat Tembilar folklore into a dance performance uses several dance elements in general, namely accompaniment music, stage setting, fashion make-up, and lighting. Archipelago folklore requires much inheritance to preserve and continue from generation to generation. Folklore-themed dance performances also contain moral, social, and other educational values.